Respon Pemberian Campuran Kompos Baglog Dengan Pupuk Kandang Sapi dan Pupuk Organik Cair (POC) Limbah Cair Pabrik Kelapa Sawit Terhadap Pertumbuhan dan Produksi Tanaman Kacang Panjang (Vigna sinensis L.). - Muhammad Rio Purnomo; Ellen Lumisar Panggabean; Siti Mardiana (Universitas Medan Area, 2020)
The research was conducted in farm experiment faculty of agriculture, the University of Medan Area The research was done by using the method of random designs that the group 's group (RAK) are composed of two treatment factors, those are: 1) Mixed of baglog compostwith cows manure (notation B) 2) Organic fertilizer, liquid waste of palm(notation K) consisting of 4 treatments, are Ko= without treatment, K1=liquid waste 50 ml/l/plants, K2=chemicals 75ml/l/plants, K3= liquid waste 100 ml/l/plants. Every treatment repeated as much as two times. The parameters in this study is focus on the diameter of steam (cm), flowering age (day), total of pods/plants (fruits), long pods/plants (cm), thick/ plants (g), and production/plot (kg). The conclusion of this study as follows: 1) giving the mixed Baglog compost with cows manure had no real effects to the diameter of steam, total pods per plants, long pods/plants, thick and plants, and productions/plot but it had real effects to flowering age. 2) giving thePOC liquid waste ofpalms had the real effects to the diameter of steam 5 MST ages, flowering age, total pods per plants, long pods per plants, thick per plants, and production. And 3) the combination both of factors had real effects to long pods per plants, and production per plot, but had no real effects to the others parameters.